Evaluation of primary school pupils with traumatized anterior permanent incisors in relation to different variables in Mosul city (Comparative study) - Ban A Salih; Aghareed G Al-Qassab (University of Mosul, College of Dentistry, 2007)
Aims: To assessing and comparing the prevalence of fractured permanent incisors between pupils of age (6-15 years) for the right and left banks of Mosul Province Materials and Methods: A cross-sectional survey carried out through clinical examination of upper and lower permanent incisors for ten thousand and 915 children and teenagers between the age 6-15 years of old, who enrolled in the public primary schools of both right and left banks of Mosul city. All the pupils examined at their schools. The diagnosis and recording of the permanent teeth crown fracture registered according to Ellis classification. Results: The most frequent traumatized teeth occurred among pupils aged 8-9 years old in both banks (49.4%). Boys demonstrated more crown fractures than girls (6.4%, 4.2% respectively), at P ≤0.001. Statistically; Pupils with class II division 1 malocclusion, inadequate upper lip coverage were significantly more affected with crown fractures (70.5% for boys, and 58.6% for girls) . The most common type of the fracture was the fracture that involve the enamel-dentin with out pulpal involvement (46.7%). The aggressive and the hyperactive behaviours of the pupils significantly showed more crown fractures, and were more common in pupils of the right bank as compared with the pupils of the left bank (P ≤0.001). While no significant difference found between pupils of both banks concerning season of the crown trauma occurrence Conclusions: The prevalence of the crown fracture was 5.4% for the total sample, while the prevalence of the crown fractures for pupils of the right bank was statistically highly significant (6.7%) than the prevalence for pupils of the left bank (4.3%).